ISLAM AS A CULTURAL CAPITAL IN INDONESIA AND THE MALAY WORLD: A Convergence of Islamic Studies, Social Sciences and Humanities (JOURNAL OF INDONESIAN ISLAM, 2017)
The phenomenon of socio-political-religious life in the Middle East is a complete contrast to the socio-political-religious life in Southeast Asia, particularly in Indonesia and in Malay world in general. The changing of socio-political leadership in Indonesia from the New Order to Reformation Order (1998) is relatively smooth, followed by the violence-free legislative election and the presidential election in 2004, 2009, and 2014. Meanwhile, the changing of socio-political leadership in the Middle East countries (the Arab Spring) are always overshadowed and followed by socio-political conflict and religious violence causing a lot of casualties. Socio-political life of the Muslim communities in Indonesia and in Malay world takes a different path from the Middle Eastern societies, and also form South Asia. Over the leadership transition in Indonesia, which is Islam as the majority, it can be run peacefully without violence and casualties. This paper will review the Indonesian Muslim intellectuals’ contribution—as an integral part of Malay world—to the development of Southeast Asian Islamic thoughts and its contribution in framing moderate-progressive Muslim in Malay world in caring for diversity, inclusion, openness, peace and harmony in the current global world.